PENGARUH IKLIM ORGANISASI DAN KEPUASAN KERJATERHADAP KINERJA PEGAWAI KANTOR KECAMATAN GUNUNG KENCANA KABUPATEN LEBAK: PENGARUH IKLIM ORGANISASI DAN KEPUASAN KERJATERHADAP KINERJA PEGAWAI KANTOR KECAMATAN GUNUNG KENCANA KABUPATEN LEBAK (Fakultas Ekonomi dan Bisnis Universitas Faletehan, 2022)
The results of the descriptive analysis show that the organizational climate, jobsatisfaction and employee performance are classified as good, which of the three variablesare in the range of a rating scale of 3.40 - 4.19. The results of multiple linear regressionobtained the regression coefficient value of the organizational climate variable of 0.212and the value of the regression coefficient of the job satisfaction variable of 0.197,each of which is positive. While the value of multiple correlation analysis (R) is 0.508which means that the magnitude of the correlation between organizational climatevariables and job satisfaction on the performance of Gunungkencana District Officeemployees is quite strong and for the coefficient of determination (R2) of 0.218 it can beconcluded that the magnitude of the influence of organizational climate andsatisfaction onthe performance of Gunungkencana District Office employees by 21.8%.As well as hypothesis testing based on the results of the t-test for theorganizational climatevariable, the value of t count > t table (2,714 > 2,024), for the job satisfaction variable,the value of t count > t table (2.101 > 2,024). And based on the results of the F test, thevalue of F count > F table (6,445 > 3,25). The conclusion of this study shows that theorganizational climate and job satisfaction either partially or simultaneously have apositive and significanteffect on the performance of the employees of the GunungkencanaDistrict Office.